Organization design as a competitive choice: An application to the study of innovation - Metin Sengul (Journal of Organization Design, 2019)
This commentary reflects on how a perspective that concentrates on the role of competitive context and sees organization design as a competitive choice may inform the research stream on the link between organization design and innovation. Focusing on multiunit firms and their formal organization, I discuss the benefits of, and the need for, adopting such an approach for this research stream, in particular, and the study of organization design, in general. I conclude by outlining some implications and directions for future research.
Keywords: 650; Organization design; Competitive context; Innovation